Percepção estética da dimensão estômio-mento para a harmonia facial - Caldas, Luciana Duarte (2014)
Facial harmony can be defined as a balanced ratio among facial thirds, and can be observed in all individuals in both front and profile view. In recent decades the impact exerted by beauty standards on society has grown substantially, underscoring the need to study this concept with keen interest. In particular the ways in which different structures can influence the standards of facial attractiveness and harmony - among these the stomion-to-menton (St-Me) dimension - should also be stressed. Thus, this study aimed to determine – with the aid of photometry - which dimensions of the stomion-to-menton (St-Me) dimension can affect aesthetics. Four models were selected, i.e., two women and two men, divided into Caucasian and Afro- Brazilian, all were mesofacial with a straight profile and featured a balanced, symmetric face. Front-view and profile images were acquired. Eight new images of each model were captured based on the original ones. These images were rendered and manipulated on the computer. The original images were alternately magnified and reduced both vertically and symmetrically by 10% and 20% of the St-Me dimension, yielding a total of 40 images. Image analysis was performed by four groups of judges (40 oral and maxillofacial surgeons, 40 orthodontists and 80 laypersons divided according to their level of education) through a questionnaire based on a visual analog scale (VAS) of attractiveness. One-factor analysis of variance (ANOVA) was applied using Tukey’s test with a confidence interval of 95%. The results showed that the original images were significantly more attractive than the others both in profile and front view. In dividing the models by gender, it was observed that for men the original front view images and those images that had been reduced by 10% were equally attractive, while in profile view there was a preference for magnified images. For women, the images with a reduced St-Me dimension were perceived as more aesthetic than those that were magnified in the same proportion. When the models were divided by ethnicity, there was a preference for reduced images of Caucasians and magnified images of Afro-Brazilians. When the groups were stratified by judge type, both laypersons and orthodontists responded consistently in terms of beauty standards. The original images were the most attractive, and the greater the distortion, the worse the values of aesthetic preference. In the group of laypersons, the original images and those manipulated by 10% were equally perceived as aesthetic by laypersons with only high school education. Among those with college education, only the original front view images and those reduced by 10% were perceived as equally aesthetic. Thus, this study found that surgeons and orthodontists have similar perceptions and preferences regarding attractiveness compared to laypersons. Furthermore, education level was an important factor in aesthetic perception. Nevertheless, all groups of judges agreed that a facial pattern with proportional, well-balanced thirds is the most aesthetic. Finally, the less proportional the St-Me dimension, the lower the attractiveness of the face.